A case of allergic blepharitis induced by a cosmetic procedure (Ukrainian Journal of Ophthalmology, 2025)
Since the beginning of this century, esthetic cosmetology has witnessed unprecedented growth, with a variety of procedures offered to enhance the customer’s appearance in a fast and non-surgical way. However, the growing demand has been paralleled by a rise in complications (particularly, ocular ones). These include allergic, mechanical and chemical lesions following eyelash extension and tinting, permanent make-up, microblading, laser-assisted eyebrow treatment and tattooing in the periocular region. Of special concern is lash and/or brow lamination, a procedure that involves the use of chemically active substances (e.g., thioglycolic acid) potentially causing inflammation, allergy, dry eye, burns and even autoimmune-like reactions. We present a case of a woman who developed allergic blepharitis and dry eye after having her first brow lamination session. Prompt diagnosis and adequate therapy including a liposomal eye spray (containing hyaluronic acid and Perilla frutescens seed extract 0.5%) led to full recovery. This case highlights the need for greater awareness among beauticians and their customers regarding potential hazards and importance of pre-procedural allergy screening and strict adherence to application protocols. It also points to the necessity for standardized post-procedural aftercare protocols.
Keywords: lash and brow lamination; allergic blepharitis,; ophthalmic complications of cosmetic procedures